Flexible graphene/cellulose composite for multimodal sensing - Ooi, Jing Quan (2023)
Graphene's distinctive 2D lattice structure and electronic properties make it an ideal material for sensor applications, with flexibility, ultra-sensitivity, fast response time, and multi-sensing capabilities. However, pristine graphene is expensive and challenging to produce. As a result, attention has shifted to graphene derivatives and composites. Oxygenated graphene flakes are not only a cheaper alternative to pristine graphene but also introduce hydrophilic properties. Cellulose is a commonly used matrix material in nanocomposites that is non-toxic and effective in creating stable dispersion. In this project, we demonstrated solution approach to nano-engineer a non-toxic sensitive composite based on graphene nanoplatelets (GNPs) and hydroxyethyl cellulose (HEC) matrix. The sensing ink was brush-coated on paper substrate, and data acquisition was performed using an Arduino project to evaluate and quantify the sensing performance towards ammonia gas, temperature, bending, and human respiration. Passivation of the sensing layer enhanced the selectivity of targeted signal. The sensing ink demonstrated distinguishable signal response towards different stimuli indicating the feasibility to detect two signals simultaneously or development of integrated sensor. This low-cost and scalable sensing ink can bridge the gap between internet of things (IoT) and current sensor technology, which is mostly bulky, non-flexible, and single sensing. The composite has the potential to serve as electronic skin to aid human health or motion monitoring, environmental monitoring, and robotics applications.